Ajuste fiscal e crescimento econômico no Brasil pós-estabilização - Lima, Bittencourt Eurípedes de (2005)
This study aims to analyze the economic repercussions of the fiscal adjustment policy (in terms of income and expenses) on economic growth in the period of inflation stabilization (post-Real Plan). The motivation of the work is based on the need to have a better understanding of the impacts of the policy of greater fiscal discipline (as a condition for maintaining price stability gains) on the real side of the economy (economic growth rates) for the economy. Brazil. The results of the empirical analysis for Brazil from 1994 Q4 to 2004 Q3 suggest that there is a significant relationship between changes in the concepts of primary deficit, real interest and nominal interest and the economy's performance in terms of changes in GDP growth rate. . These results suggest the existence of an important relationship between fiscal adjustment policies and their impacts on the real side of the economy. One of the ways in which the result described above can be thought of is the close relationship between fiscal adjustment, interest rates and how they relate to the economy's performance since it is partially conditional on the payment of interest on the economy. It has a close link with the public finance situation, which is one of the dimensions of the global macroeconomic situation to be considered. Finally, the relevance of the tax policy in the sense that there are indications of its relationship with the growth rate of the economy.